A Study of Prognostic Indicators in Oral Cavity Squamous Cell Carcinoma in a Tertiary Care Institution - Jadhav, Asawari Bharat; Bharambe, Bhavana Madhukar; Ahire, Dipali Suresh; Trivedi, Saumya; Bute, Rajeshwar Suresh (Annals of Pathology and Laboratory Medicine, 2025)
Background: Oral carcinoma is ranked as the sixth most common type of cancer worldwide, with India harboring one-third of the overall burden. Factors like smoke, tobacco, asbestos, silica, and other carcinogenic components may play a part. Late-stage detection leads to five-year survival rates of around 20% only. Hence, this study was designed to analyze the prognostic factors for oral squamous cell carcinoma (OSCC) at a tertiary care hospital. The aims were to assess the prevalence and frequency of OSCC, identify prognostic indicators in the specimens received to predict outcomes, and follow up wherever possible. Materials and Methods: Parameters like depth of invasion, worst pattern of invasion, lymphocyte response, perineural invasion, resection margin status, lymphovascular invasion, and extranodal extension were studied. Results: The majority of the study had a type 1 WPOI and type 1 LHR response. Perineural invasion, lymphovascular invasion, and extranodal spread were seen in advanced cases. Conclusion: Key factors contributing to poor prognosis included age, smoking or tobacco use, and a higher depth of invasion (>10 mm). Perineural or lymphovascular/extranodal spread and a higher grade of WPOI were significantly associated with poor prognosis.